Perception of risk and shared decision making process in multiple sclerosis. (1st February 2017) - Cocco, Eleonora; Caoci, Alberto; Lorefice, Lorena; Marrosu, Maria Giovanna
ABSTRACT: Introduction : Multiple sclerosis (MS) treatment has changed considerably in recent years thanks to the introduction of ever-more-powerful drugs. Unfortunately, the higher efficacies of these therapies are associated with increased risks of severe adverse events. In this scenario, neurologists and persons with MS (pwMSs) must now balance benefits and risks when making decisions regarding MS management. Areas covered : This review highlights the importance of the risk perception of pwMSs and their neurologists in the shared decision-making process in MS management, taking into account different ways improve the empowerment and engagement of pwMSs. Expert commentary : The shared decision-making process in MS is strongly influenced by an individual's risk perception, which is dynamic and influenced by the personal, emotional, social, and experiential factors of both the pwMSs and neurologists.